Prospek Sistem Pendidikan Vokasi di Indonesia Abad-21 - Zukna, Irawan; Sassi, Komarudin (LPPM Institut Pendidikan Nusantara Global, 2024)
The industrial revolution 5.0 necessitates a super-smart society for all elements of society, including the world of vocational education in Indonesia in the 21st century. Because the era of industrial revolution 5.0 has the consequence of a skilled workforce who is familiar with various digital technologies as well as opportunities for vocational education in Indonesia. Indonesia has prospects in developing vocational education, because it is supported by the following factors; First, the government has paid greater attention to the development of vocational education through various policies and programs. Second, the business world is increasingly realizing the importance of collaborating with vocational education institutions to obtain competent human resources. Third, public interest in vocational education is increasing along with awareness of wider job opportunities. Through the descriptive-analysis method, it was found that in order to realize the prospects for a 21st century vocational education system, the Indonesian government is strengthening cooperation with various industrial worlds (DUDI), fulfilling practicum instruments, and updating the vocational curriculum to adapt to the needs of industry 5.0.